2018
DOI: 10.1103/physreve.97.013201
|View full text |Cite
|
Sign up to set email alerts
|

Causes of plasma column contraction in surface-wave-driven discharges in argon at atmospheric pressure

Abstract: In this work we compute the main features of a surface-wave-driven plasma in argon at atmospheric pressure in view of a better understanding of the contraction phenomenon. We include the detailed chemical kinetics dynamics of Ar and solve the mass conservation equations of the relevant neutral excited and charged species. The gas temperature radial profile is calculated by means of the thermal diffusion equation. The electric field radial profile is calculated directly from the numerical solution of the Maxwel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 56 publications
9
39
0
Order By: Relevance
“…However, in Golubovskii et al (2020), this effect seems to be due to the low values of E/n g in the radial edges, as E/n g is theoretically estimated to have a significantly concave distribution in that work. The concave shape of E/n g is in agreement with the experimental measurements and simulations of concave profiles of T e in Kabouzi et al (2007), Gregório et al (2010), Golubovskii et al (2011), Gregório et al (2012), Golubovskii et al (2017), Ridenti et al (2018), Zhong et al (2019). In fact, the simulations in Ridenti et al (2018) have shown that T e in Thomson scattering measurements, such as those in van Gessel et al (2012), Carbone et al (2012), has a convex radial profile due to the Maxwellian assumption of this diagnostic, while T e obtained from the calculated EEDF (2/3 of mean electron energy) actually has a concave radial profile, as does E/n g .…”
Section: Introductionsupporting
confidence: 87%
“…However, in Golubovskii et al (2020), this effect seems to be due to the low values of E/n g in the radial edges, as E/n g is theoretically estimated to have a significantly concave distribution in that work. The concave shape of E/n g is in agreement with the experimental measurements and simulations of concave profiles of T e in Kabouzi et al (2007), Gregório et al (2010), Golubovskii et al (2011), Gregório et al (2012), Golubovskii et al (2017), Ridenti et al (2018), Zhong et al (2019). In fact, the simulations in Ridenti et al (2018) have shown that T e in Thomson scattering measurements, such as those in van Gessel et al (2012), Carbone et al (2012), has a convex radial profile due to the Maxwellian assumption of this diagnostic, while T e obtained from the calculated EEDF (2/3 of mean electron energy) actually has a concave radial profile, as does E/n g .…”
Section: Introductionsupporting
confidence: 87%
“…Our modeling results show the axial distribution of argon atomic (Ar + ) and two molecular (Ar 2 + and Ar 3 + ) ions along the plasma column in the three discharge tubes (Figure 7). As it can be seen, the molecular Ar 2 + ion has a much higher concentration than the other two ions in all tubes, which is in good agreement with the prediction in [48,49]. The highest concentration of Ar 2 + ion is in the tube with the smaller inner diameter (8 mm/2 mm).…”
Section: Effects Of the Dielectric Tube Inner Diameter On The Plasma ...supporting
confidence: 86%
“…Our investigation shows that the appearance of the second filament happens at a lower wave power when the inner diameter of the discharge tube is smaller. It is shown by experimental [48] and radial modeling [49] investigations that the molecular argon ions play a critical role in the radial contraction of argon microwave discharges at atmospheric pressure. Our modeling results show the axial distribution of argon atomic (Ar + ) and two molecular (Ar 2 + and Ar 3 + ) ions along the plasma column in the three discharge tubes (Figure 7).…”
Section: Effects Of the Dielectric Tube Inner Diameter On The Plasma ...mentioning
confidence: 99%
“…In each case, fluctuating filaments are visible both in the plasma inside the box and at the outlet. Such filamentary plasma structure is typical for the radio and microwave frequency argon discharges at atmospheric pressure and is related to the electromagnetic skin effect, non-uniform gas heating, presence of molecular ions, and electron energy distribution function [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%